PROBLEMATIKA PEMBELAJARAN MATEMATIKA SISWA KELAS IV SD - Mariana Jediut; Fransiska Jaiman Madu; Marlinda Mulu (PGSD UNIKA SANTU PAULUS RUTENG, 2022)
This study aims to describe the problematics of fourth grade students of Wae Ri'i elementary school in learning mathematics, along with the factors that influence these problems. This research is a qualitative research. Data collection uses observation and interview techniques. Then the data were analyzed using techniques proposed by Milles and Huberman which includes data reduction, data display, and drawing conclusions. The results show that are several problems experienced by students in learning mathematics. These problems include students being less able to complete multiplication and division operations, less able to apply formulas in solving problems given by the teacher, and student attitudes in learning mathematics tend to be negative as indicated by the students' lack of seriousness in learning. The factors that cause these problems are 1) internal factors which include the lack of students' understanding of the concepts of multiplication and division; 2) external factors such as noise created by students, lack of use of instructional media, and lack of teacher's explanation of the mathematical concepts being learned.